Case study: Beverage temperature at aid stations in Ironman triathlon - Burdon, C. A.; Johnson, N. A.; Chapman, P. G.; Che Muhamed, A. M.; O'Connor, H. T. (International Journal of Sport Nutrition and Exercise Metabolism, 2013)
Purpose: The aim of this study was to measure the effect of environmental conditions and aid-station beverage-cooling practices on the temperature of competitor beverages. Methods: Environmental and beverage temperatures were measured at three cycling and two run course aid stations at the 2010 Langkawi, Malaysia (MA), and Port Macquarie, Australia (AU), Ironman triathlon events. To measure the specific effect of radiant temperature, additional fluid-filled (600 ml) drink bottles (n = 12) were cooled overnight (C) and then placed in direct sun (n = 6) or shade (n = 6) near to a cycle aid station at AU. Results: During both events, beverage temperature increased over time (p < .05) as environmental conditions, particularly radiant temperature increased (p < .05). Mean beverage temperature ranged between 14-26°C and during both events was above the palatable range (15-22°C) for extended periods. At AU, bottles placed in direct sunlight heated faster (6.9 ± 2.3 °C/h) than those in the shade (4.8 ± 1.1°C/h, p = .05). Conclusion: Simple changes to Ironman aid- station practices, including shade and chilling beverages with ice, result in the provision of cooler beverages. Future studies should investigate whether provision of cool beverages at prolonged endurance events influences heat-illness incidence, beverage-consumption patterns, and competitor performance.